FORMATION OF PROFESSIONAL THINKING AS A PREREQUISITE FOR THE SUCCESSFUL ACTIVITY OF A SPECIALIST (Conferencea, 2022)
Any profession places high demands on the thinking of a specialist. It should be purposeful, flexible, deep, mobile, fast and accurate. The role of independent thinking and foresight, the ability to find the right solution with a lack of data has increased.